Focus in bilingual Spanish: A state of the science review - Hoot, Bradley (Isogloss, 2025)
Bilingual grammars differ systematically from those of monolinguals, but not all areas are affected equally. One linguistic feature that has been claimed to be especially vulnerable to divergence in bilinguals is information structure, which includes constructions in which speakers adapt sentences to the discourse context by manipulating syntax or prosody to mark certain constituents as prominent. A constituent expressing new information, called the focus of the sentence, may be realized in a prominent position like the right or left edge (e.g., ¿Quién tosió? Tosió [Juan]F. ‘Who coughed? [Juan]Fcoughed.’). Research on focus expression in bilingual grammars has expanded substantially in the past three decades, with data from Spanish playing a key role. As the evidence accumulates, it may now be fruitful for the field to pause and take stock of our progress. The goal of this paper is to review the current state of research on focus realization in bilingual Spanish. I synthesize this growing body of scholarship, examining 41 quantitative or experimental studies of the realization of the information-structural category of focus. I conclude that (a) the bulk of the evidence suggests information focus in Spanish does not in fact present special difficulty for bilinguals, regardless of speaker background or methods; (b) the evidence is more mixed for contrastive focus, although many studies find it can be acquired; and (c) where differences are found, prosody may be the area most vulnerable to cross-linguistic influence. After examining the evidence, I make several recommendations for future research.